2015
DOI: 10.29252/jhehp.1.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Study of Screening Mammography Frequency and Related Variables in Women Referring to the Mammography Center, Mousavi Hospital, Zanjan

Abstract: Background: Breast cancer is the most common cancer found in women, and screening is the best way to make an early diagnosis. The aim of this study was to determine the rate of screening mammography and related variables in the mammography center of Mousavi Hospital, located in Zanjan, Iran. Methods: This was a prospective descriptive study. Study sample size was 526 women who were selected by a convenience sampling method. Data collection instrument was a multisection questionnaire and this was completed by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…BC detection rate has been reported in some studies with different designs. In a cross-sectional study achieved on females admitted to the Mammo center of a hospital, BC was detected in 2.3% of 526 screened patients (111). BC detection rate of non-diagnostic mammography in 9395 subjects was 8.5 per 1000 Mammo (112).…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…BC detection rate has been reported in some studies with different designs. In a cross-sectional study achieved on females admitted to the Mammo center of a hospital, BC was detected in 2.3% of 526 screened patients (111). BC detection rate of non-diagnostic mammography in 9395 subjects was 8.5 per 1000 Mammo (112).…”
Section: Resultsmentioning
confidence: 96%
“…They recorded 996 Sono, and 636 Mammo reports with 40 and 183 abnormal cases, respectively and found one BC by performing 14 FNA (114). The screening Mammo rate, diagnostic sonography rate, biopsy rate, and abnormality rate were 27.4%, 26%, 1.4%, and 33% in a screening project, respectively (111). Results of a study indicated that the mean scores of females' breast cancer screening belief and multidimensional health locus of control were 40.72±10.41 and 67.78±17.67, respectively (115).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 100 106 ] The participation rate in the screening program was reported from 3.8% to 16.8% in two studies. [ 52 107 ] BC detection rate has been reported in some studies with different designs. In a cross-sectional study on females admitted to the mammography center in a hospital, BC was detected in 2.3% of 526 screened patients.…”
Section: Resultsmentioning
confidence: 99%